Literasi Teknologi Informasi dan Komunikasi Siswa SDI Lukman al-Hakim Mataram: Model Komunikasi dan Pendampingan - Ahyar, Ahyar (Jurnal Komunikasi Islam, 2017)
This study discusses the communication model and assistance pattern of information and communication technology (ICT) literacy for students conducted by teachers in SDI Lukman al Hakim Hidayatullah Mataram. This study is a descriptive qualitative research using participatory observation and in-depth interviews for two months. The study finding shows there are three models of assistance in ICT literacy, ie individual, group, and synergistic teacher-guardian. While the communication models used by teachers are linear and transactional communication models. By utilizing those models, ICT usage in this school has contributed in positive and significant way to support the process of increasing knowledge, learning experience, and internalization of students' tauhid.